Case Report: Long lasting response with TKI for combined hepatocellular-cholangiocarcinoma - Deiana, Chiara; Palloni, Andrea; Mosca, Mirta; Vasuri, Francesco; Chillotti, Stefano; Tavolari, Simona; De Biase, Dario; Frega, Giorgio; Giovannetti, Elisa; Brandi, Giovanni (Frontiers in Oncology, 2025)
Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a rare primary liver cancer, with intermediate biological characteristics between hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA). Given its rarity and the lack of robust data from randomized clinical trials, treatment is not standardized, and the choice on how to best manage the disease is left to the expertise of each institution. In the metastatic setting, given the more aggressive behavior of the CCA component, the usual approach is to start treatment with chemotherapy instead of tyrosine-kinase inhibitors (TKIs). We present a case report on a Caucasian male with a poor response to first-line treatment with chemotherapy directed against CCA, but with an excellent and long overall survival (OS) of 71 months, thanks to HCC-directed treatment with TKI. Here, we highlight the difficulty in selecting an appropriate treatment upfront for this rare cancer and we also discuss future perspectives regarding predictive tools, especially considering the recent genomic analysis of cHCC-CCA, and regarding the potential use of immunotherapy and target therapy.